1985
DOI: 10.2466/pms.1985.61.3f.1303
|View full text |Cite
|
Sign up to set email alerts
|

Role of Visual Richness in Picture Recognition Memory

Abstract: 25 fourth graders, 21 eighth graders, and 21 college students were shown slides of objects presented as color photographs, black-and-white photographs, simple outline drawings, or printed words. After an 8-wk. delay, students were asked to discriminate the study slides from similar distractor slides. No significant differences were found among the types of pictures. Recognition of black-and-white photographs was superior to words.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…One aspect of realism is the detail observable in the learning materials. Researchers have studied learning stimuli ranging from real objects that depict the greatest amount of detail to schematic diagrams that show the least amount of detail, with photographs and more detailed drawings falling in between (e.g., Anglin & Levie, 1985;Dwyer, 1972;Holliday, Brunner, & Donais, 1977;Joseph & Dwyer, 1984). Another particularly important aspect of realism in the case of mechanical systems is whether or not materials show movement of the systems.…”
Section: Effects Of Media On Learning Outcomesmentioning
confidence: 99%
“…One aspect of realism is the detail observable in the learning materials. Researchers have studied learning stimuli ranging from real objects that depict the greatest amount of detail to schematic diagrams that show the least amount of detail, with photographs and more detailed drawings falling in between (e.g., Anglin & Levie, 1985;Dwyer, 1972;Holliday, Brunner, & Donais, 1977;Joseph & Dwyer, 1984). Another particularly important aspect of realism in the case of mechanical systems is whether or not materials show movement of the systems.…”
Section: Effects Of Media On Learning Outcomesmentioning
confidence: 99%
“…The result affirms a study by Joseph and Proffitt (1996), in which they concluded that stored color knowledge was more influential in object recognition than surface color. However, an opposing result is forwarded by Anglin and Levie (1985) in that enhancements of B & W photographs such as shading, detail, and color did not increase the likelihood of memory recall.…”
Section: Introductionmentioning
confidence: 83%
“…This is not to say that scholars have ignored the ways in which visual stimuli are mentally received; indeed, considerable bodies of scholarship in psychology and social psychology indicate that visual images are recognized and subsequently recalled more quickly, and for a lengthier duration, than are lexical words (e.g. Anderson and Paulson, 1978;Anglin and Levie, 1985;Borges et al, 1977;Burton and Bruning, 1982;Emmerich and Ackerman, 1979;Gehring et al, 1976;Jenkins et al, 1967;Kaplan et al, 1968;Paivio, 1976;Park et al, 1983). …”
Section: Literature Reviewmentioning
confidence: 99%